Overview of Landslide Trends in the World and in Ukraine - Olishevska, S. O. (Science and Transport Progress, 2024)
Purpose. The main purpose of the study is to systematize and analyse in-depth current trends in the field of landslide prevention and development in different countries of the world, especially in Ukraine, as well as to consider and highlight the main factors that cause landslides, and to study in detail the methods of their prediction and minimization of relevant risks. Methodology. Landslides are a serious geological hazard. Currently, there is a tendency to increase the frequency of landslides due to anthropogenic impact worldwide. The natural processes of the geological environment, together with the development of mineral deposits, massive and large-scale land development, lead to the intensification of landslide processes. The cause of landslide formation is an imbalance between the shear force of gravity and the retaining forces. Findings. The number of landslides in recent years has been analysed and their distribution on different continents has been considered in detail. The causes of landslides in Ukraine and other countries of the world are identified and systematized. The urgency of the problem of landslide phenomena in Ukraine is considered, and the need for progressive study of landslide formation processes in order to prevent them is emphasized. The importance of continuous monitoring of slope stability is emphasized to reduce risks and improve safety. Originality. A comprehensive study of current trends in the occurrence and development of landslides in different countries of the world and Ukraine in particular was carried out, taking into account the latest advances in the field of geology, geomechanics and construction. Based on the analysis, conclusions were drawn about the need for progressive study of landslide processes in order to prevent them. Practical value. The results of the review of landslide prevention trends can be effectively used to improve natural risk management strategies, as well as to develop new and improve existing engineering measures aimed at preventing landslides. This, in turn, will help to improve the safety of both the population and critical infrastructure.